How students switch on and switch off in mathematics: exploring patterns and predictors of (dis)engagement across middle school and high school. Issue 4 (21st April 2019) - Collie, Rebecca J.; Martin, Andrew J.; Bobis, Janette; Way, Jennifer; Anderson, Judy
Abstract: Using growth modeling, this study examined trajectories of 'switching on' (aspirations) and 'switching off' (disengagement) in mathematics across middle school and high school. In addition, guided by principles under expectancy-value theory, the study sought to determine the extent to which patterns of growth differed by motivation (self-efficacy and valuing) and socio-educational attributes (gender, language background, and achievement). The sample comprised 194 students from four schools who participated in three rounds of data collection across five academic years of their schooling, spanning middle school and high school. In the main, mathematics aspirations declined over time while mathematics disengagement increased. However, initial levels of aspirations and disengagement and their rates of change over time were impacted by motivational and socio-educational factors. Salient findings and their implications for educational assessment and practice are discussed.